A Cross-Sectional Needs Assessment of Adolescent Physical Activity in the Early Nutrition Transitioning Country of Haiti (P16-006-19). (13th June 2019) - Becker, Haley; Dulience, Sherlie Jean-Louis; Philippe, Allan; Siqueira-Reis, Rodrigo; Brownson, Ross; Lesorogol, Carolyn; Salvo, Deborah; Iannotti, Lora
Abstract: Objectives: An exploratory assessment of physical activity (PA) to identify covariates of PA behaviors in Haitian adolescents. Methods: Students from two urban schools participated in two different data collection methodologies: a self-reported survey ( n  = 100) assessing school, transportation, and leisure-time PA; an objective accelerometry study ( n  = 55). Self-reported diet behaviors were also collected. Parent and non-parent caregivers reported demographic data. Logistic regression identified potential correlates of PA; PA was operationalized as meeting the World Health Organization's recommendation (WHO REC) of ≥60 minutes of moderate/vigorous PA per day for adolescents. Results: Self-reported data. The school PA model showed age (OR = 2.03; 95% CI = 0.66, 6.31), gender (OR = 1.41; 95% CI = 0.40, 4.97), and dietary diversity score ([DDS]; OR = 1.49; 95% CI = 1.17, 1.90) were significantly associated with WHO REC. Age (OR = 1.90; 95% CI = 1.55, 6.53), gender (OR = 1.22; 95% CI = 1.19, 3.03), DDS (OR = 1.25; 95% CI = 0.99, 1.57), and caregiver's occupation in the market (OR = 5.66; 95% CI = 1.27, 25.20) were significant correlates of WHO REC in the transportation PA model. The leisure-time PA model found gender (OR = 3.95; 95% CI = 1.09, 14.33), DDS (OR = 1.37; 95% CI = 1.09, 1.74), and bringing a snack/meal to school (OR = 4.17, 95% CI = 1.18, 14.67) to be significant covariates of WHO REC. Objective data. The model of accelerometry PA identified age (OR = 4.17; 95% CI = 1.31, 55.79), gender (OR = 48.19; 95% CI = 22.16, 77.92; female reference group), DDS (OR = 4.48; 95% CI = 1.12, 16.76), and household access to a flush toilet (OR = 0.03; 95% CI = 0.46, 64.45) as significant correlates of WHO REC. Conclusions: As nutrition transition is underway in Haiti, so is the onset of the dual burden of malnutrition; PA can alleviate the negative health consequences of both phenomena, but heretofore such data have been unavailable for Haiti. Results support a) early adoption of policies and programs for PA and nutrition together and b) future investigation into Haitian PA behaviors and their sociocultural determinants. Funding Sources: This study was funded by the Public Health Cubed Grant of the Washington University Institute of Public Health and the Brown School of Social Work International Dissertation Research Award.